2014
DOI: 10.1080/09603123.2014.989493
|View full text |Cite
|
Sign up to set email alerts
|

Mine dumps, wheeze, asthma, and rhinoconjunctivitis among adolescents in South Africa: any association?

Abstract: The study investigated the association between community proximity to mine dumps, and current wheeze, rhinoconjunctivitis, and asthma among adolescents. This study was conducted during May–November 2012 around five mine dumps in South Africa. Communities in close proximity to mine dumps had an increased likelihood of current wheeze OR 1.38 (95 % CI: 1.10–1.71), rhinoconjunctivitis OR 1.54 (95 % CI: 1.29–1.82), and a protective association with asthma OR 0.29 (95 % CI: 0.23–0.35). Factors associated with health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 56 publications
3
25
0
Order By: Relevance
“…This suggest that mine dumps can have an influence on the indoor air pollution levels in the houses and schools of the nearby communities. A cross-sectional study conducted in the communities located close to mine dumps in South Africa showed that a significant number of residents still use coal or fossil fuel as the main residential heating or cooking fuel type; [18, 46] probably contributes to the ambient levels of SO 2 in these communities. Research studies have indicated that asthmatics are very sensitive to inhaled SO 2 , and experience changes in pulmonary function and respiratory symptoms after periods of exposure to SO 2 as short as 10 min is sufficient to induce broncho-constriction [4750].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggest that mine dumps can have an influence on the indoor air pollution levels in the houses and schools of the nearby communities. A cross-sectional study conducted in the communities located close to mine dumps in South Africa showed that a significant number of residents still use coal or fossil fuel as the main residential heating or cooking fuel type; [18, 46] probably contributes to the ambient levels of SO 2 in these communities. Research studies have indicated that asthmatics are very sensitive to inhaled SO 2 , and experience changes in pulmonary function and respiratory symptoms after periods of exposure to SO 2 as short as 10 min is sufficient to induce broncho-constriction [4750].…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have shown that mine dumps are a major contributor to particulate matter air pollution to surrounding communities and that proximity is associated [16] with increased risk asthma symptoms. [17, 18] Taking into consideration that school children spend one-third of their total time inside school buildings, it is evident that air quality inside the classrooms should be of concern [5, 19, 20]. Whether it is indoor or outdoor, PM 10 may have adverse biological effects when exposures are prolonged in children [21].…”
Section: Introductionmentioning
confidence: 99%
“…The community included in the study is located near a busy highway, indicating that traffic is also a major contributor to ambient air pollution in this area. A cross-sectional study conducted in South Africa showed that heavy truck was a risk factor for asthma symptoms in communities located nearby mine dumps than those far away (Nkosi et al, 2015). All children in the study area are exposed to the ambient air pollution, resulting in a large number of children affected.…”
Section: Discussionmentioning
confidence: 95%
“…Children with asthma were identified from a selfadministered questionnaire survey based on the International Study of Asthma and Allergies in Childhood (ISAAC) (Ellwood et al, 2005). The ISAAC study was carried out in the previous year, It included 400 secondary school children in Noordgesig (Nkosi et al, 2015). For the present study, children who had given a positive response to the question "Has a doctor/physician ever told you that you had asthma?"…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation